Pengaruh Lingkungan Kerja, Motivasi Kerja, Dan Disiplin Kerja Terhadap Produktivitas Karyawan Pada BLP Property - Rahmansyah, Gheofani Oky; Cahyadi, Nur (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2023)
This article or writing aims to determine the influence of the work environment, work motivation, and work discipline on the productivity of BLP Property employees. This research was obtained from primary data and the research population was 30 employees, then used a saturated sampling technique. Data was collected through distributing research questionnaires, by submitting written statements to BLP Property employee respondents and analyzed quantitatively. Testing this research hypothesis uses Partial Least Square (PLS) version 4. This study shows the results that work environment variables and work discipline variables have no effect on employee productivity variables and work motivation variables have a significant effect on employee productivity variables.